Short- and mid-term outcomes of multisystem inflammatory syndrome in children: a longitudinal prospective single-center cohort study - Roge, Ieva; Kivite-Urtane, Anda; Smane, Liene; Meiere, Anija; Klavina, Lizete; Barzdina, Elza; Pavare, Jana (Frontiers in Pediatrics, 2023)
Background: Multisystem inflammatory syndrome in children (MIS-c) emerged during the coronavirus disease 2019 pandemic and is associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Despite the extensively studied clinical manifestation of acute condition, the short-and long-term effects of MIS-c on children's health are unknown.This was a prospective longitudinal cohort study. Children aged ˂18 years who met the Centers for Disease Prevention and Control (CDC) diagnostic criteria and who were admitted to the Children's Clinical University Hospital of Latvia (CCUH) between July 1, 2020, and April 15, 2022, were enrolled in the study. An outpatient follow-up program was initiated in July 2020. All children were evaluated at 2 weeks, 2 months (1-3 months), and 6 months (5-7 months) after discharge. The face-to-face interviews comprised four domains as follows: symptom assessment, physical examination, laboratory testing, and cardiological investigation (including electrocardiogram (ECG) and echocardiography (echo)).Results: Overall, 21 patients with MIS-c were enrolled. The median age of the study group was 6 years. At the 2-week follow-up, almost half of the patients (N=10, 47.6%) reported exercise intolerance with provoked tiredness. Laboratory tests showed a considerable increase in blood cell count, with a near doubling of leukocyte and neutrophil counts and a tripling of thrombocyte levels. However, a decline in the levels of inflammatory and organ-specific markers was observed. Cardiological investigation showed significant improvement with gradual resolution of the acute-phase pathological findings. Within 2 months, improvement in exercise capacity was observed with 5-fold and 2-fold reductions in physical intolerance (N=2, 9.5%) and physical activity-induced fatigue (N=5, 23.8%), respectively. Normalization of all blood cell lines was observed, and cardiological investigation showed no persistent changes. At the 6-month visit, further improvement in the children's exercise capacity was observed, and both laboratory and cardiological investigation showed no pathological changes.Conclusions: Most persistent symptoms were reported within the first 2 weeks after the acute phase, with decreased physical activity tolerance and activity-induced fatigue as the main features. A positive trend was observed at each follow-up visit as the spectrum of the children's complaints decreased. Furthermore, rapid normalization of laboratory markers and cardiac abnormalities was observed.